2014
DOI: 10.5121/ijccsa.2014.4503
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling In Cloud Computing

Abstract: Cloud computing is an emerging technology. It process huge amount of data so scheduling mechanism works as a vital role in the cloud computing. Thus my protocol is designed to minimize the switching time, improve the resource utilization and also improve the server performance and throughput. This method or protocol is based on scheduling the jobs in the cloud and to solve the drawbacks in the existing protocols.Here we assign the priority to the job which gives better performance to the computer and try my be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Other work in scheduling such as [3] takes into consideration tasks priorities then assign them to be executed over the allocated resources. If there more than one task for each resource, it will be scheduled with different methods depending on what is better for each resource.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other work in scheduling such as [3] takes into consideration tasks priorities then assign them to be executed over the allocated resources. If there more than one task for each resource, it will be scheduled with different methods depending on what is better for each resource.…”
Section: Discussionmentioning
confidence: 99%
“…Nodes or virtual machines (VMs) are the virtual resources that are assigned to consumers for running the service and executing tasks [2]. Scheduling is a very complex operation in cloud computing used to allocate resources, improving server utilisation, enhance service performance, and executing tasks [3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tripathy and Patra [6] give an overview of scheduling tasks (jobs) with priorities. Their aim is to run all high priority tasks first over the number of resources required.…”
Section: Ssm Vs Othersmentioning
confidence: 99%
“…As a start, the task identified with the following attributes jobi(j,k,l): i for job or task id, j for resources required, k for task duration, and l for task priority. Then the following service request given: (6,10,5) • job3 (2,5,4) • job4(2,5,2) Fig 9 shows how tasks are running over resources.…”
Section: Ssm Vs Othersmentioning
confidence: 99%
“…The results have shown that Rank based task scheduler gives high performance than existing space-shared and time-shared task schedulers. Tripathy and Patra [8] have discussed the scheduling in cloud computing. Cloud computing is a developing innovation.…”
Section: Literature Reviewmentioning
confidence: 99%